Enhanced γ-phase crystallinity of Al2O3 frameworks at the concave surface of PS-b-PEO templated spherical pores. Issue 21 (19th April 2021) - Islam, Md. Saidul; Wakabayashi, Ryutaro; Kimura, Tatsuo
Abstract : Pore surfaces having higher curvatures become dense by shrinking Al2 O3 frameworks with condensation and crystallization by thermal treatment, being useful as a rational guideline for the enhancement of its γ-phase crystallinity. Abstract : The crystallinity of inorganic solids like metal oxides after the porosity design is the crucial factor that should be investigated for enhancing their physicochemical properties. In most cases, metal oxide frameworks around mesopores, that are designed through the supramolecular mediated approach, are resulted to be amorphous. Accordingly, a rational guideline has been required for enhancing the crystallinity of frameworks at such concave surfaces. We have so far surveyed a crystallization behavior of alumina (Al2 O3 ) frameworks to its γ-phase around spherical mesopores (∼40 nm) and discussed further transition to the α-phase around much larger pores (∼200 nm). In this paper, we prepared new and helpful Al2 O3 powders having PS- b -PEO templated pores (∼25 nm and ∼75 nm) smaller than those of our previous case. After careful discussion of the pore size variation by considering the molecular structure of PS- b -PEO, we explained the crystallization behavior of the Al2 O3 frameworks to enhance its γ-crystallinity. This knowledge is quite beneficial for designing highly porous Al2 O3 powders with abundant crystallinity for use as catalyst supports, which is very useful for assessing synthetic procedures of other mesoporous metal oxides having high crystallinity.